The Safety and Efficacy of Ultrasound-Guided Bilateral Dual Transversus Abdominis Plane (BD-TAP) Block in ERAS Program of Laparoscopic Hepatectomy: A Prospective, Randomized, Controlled, Blinded, Clinical Study - Zhang J; Liu T; Zhou H; Fei Y; Yu X (Dove Medical Press, 2020)
Jun Zhang, Tieshuai Liu, Haiyan Zhou, Yue Fei, Xin Yu Department of Anesthesiology, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Xin YuDepartment of Anesthesiology, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, 3 Qingchun Road East, Jianggan District, Hangzhou 310016, Zhejiang, People’s Republic of ChinaTel +86 13588708514Fax +86 0571-86006662Email xinxin_yu@zju.edu.cnPurpose: Postoperative pain management for patients undergoing hepatic resection is still a challenge due to the risk of perioperative liver dysfunction. The transversus abdominis plane (TAP) block is a promising regional analgesic technique. However, the correct guidelines regarding the dose and regimen of local anesthetics in patients undergoing hepatic resection have yet to be established completely. This study aimed to evaluate the safety and efficacy of ultrasound-guided BD-TAP block with a large dose of ropivacaine in laparoscopic hepatectomy.Patients and Methods: This prospective, blinded, randomized, controlled study was conducted with 50 patients who were scheduled for selective laparoscopic hepatectomy. Patients who received a BD-TAP block (3 mg/kg of ropivacaine diluted to 60 mL) with general anesthesia were categorized into the BD-TAP block group (n = 25), and those who received general anesthesia were categorized into the control group (n = 25). The primary outcomes were consumption of sufentanil within 48 hours post-operation and plasma ropivacaine concentration. The secondary outcomes were the severity of pain (at rest and upon coughing), nausea and/or vomiting, and quality of recovery.Results: Compared with the control group, the patients in BD-TAP block group had a significant reduction of postoperative sufentanil consumption at 2 hours (P = 0.019), 24 hours (P = 0.001), and 48 hours (P = 0.001), and the visual analog scale (VAS) scores on coughing were significantly lower at postoperative 2 hours (P = 0.004). There were no statistically significant differences in postoperative nausea and/or vomiting, flatus, catheter removal, off-bed activity, liver function, or postoperative hospital stay. The mean peak total ropivacaine concentration was 1,067.85 ng/mL, which occurred 1 hour after administering the block, and mean free ropivacaine concentration was 52.32 ng/mL. The highest individual peak plasma concentration was 2,360.90 ng/mL at 45 min postinjection, and the free ropivacaine concentration was 139.29 ng/mL.Conclusion: Ultrasound-guided BD-TAP block provides effective postoperative analgesia after laparoscopic hepatectomy. This study also confirms that ultrasound-guided BD-TAP blocks with 3 mg/kg ropivacaine during laparoscopic hepatectomy almost never results in the plasma ropivacaine concentrations associated with neurotoxicity.Keywords: ropivacaine, laparoscopic hepatectomy, BD-TAP block, neurotoxicity